Spiritual care in a non-religious context – conference report and several reflections on the topic: Spiritual care in a non-religious context – conference report and several reflections on the topic (Paliativní medicína, 2025)
What does spiritual care look like for patients who do not identify with any religion, with any church? What can be expected from such care, what are its benefits and risks? Should it be a regular part of care for the sick and dying? A conference organized jointly by both Czech associations of health care chaplains on June 10, 2025 at the Hospital of the Sisters of Mercy of St. Charles Borromeo in Prague sought to answer these questions. In addition to the report from the conference, we also bring several related reflections from hospital chaplains and one "non-believing" recipient of their care.
Keywords: spiritual care; health care chaplaincy; categorical pastoral care; non-religious care